Neoliberalism Anchorages – Neoliberalism is not a Religion, it is a System (Economic and Political Thought, 2013)
The treatment of neoliberalism as religion leads to a situation in whichthere are almost no people in the world who admit that they are neoliberals.Although it is common in Poland, especially in political parties, it isalso inappropriate to understand neoliberalism as liberalism. As a result,calling people ‘liberals’ sounds like calling them names. When Donald Tuskdeclared his retreat from the liberal doctrine and feeling attracted to socialdemocracy, he did not want to be a ‘liberal’, and the main Polish neoliberal,Leszek Balcerowicz, did not want to admit that he was one and he decidedto ‘move’ towards a target system in the libertarian ideology that takes theform of anarcho-capitalism. The author advances and justifies a thesis thatthe system of neoliberalism alone has its anchorage not only in libertarianismbut also in the financial spheres and because of that, in spite of the fact that itcaused a disastrous crisis with its first victim – the United States, the efficientsystematic reforms in this state do not lead to liberalism, which – in accordancewith economic sciences – would be in agreement with the principlesof the mainstream.